Optic nerve head perfusion in normal eyes and eyes with glaucoma using optical coherence tomography-based microangiography - Chen, Chieh-Li; Bojikian, Karine D.; Gupta, Divakar; Wen, Joanne C.; Zhang, Qinqin; Xin, Chen; Kono, Rei; Mudumbai, Raghu C.; Johnstone, Murray A.; Chen, Philip P.; Wang, Ruikang K. (Quantitative Imaging in Medicine and Surgery; Vol 6, No 2 (April 28, 2016): Quantitative Imaging in Medicine and Surgery, 2016)
Background: To investigate the differences of perfusion in the optic nerve head (ONH) between normal and glaucomatous eyes using optical microangiography (OMAG) based optical coherence tomography (OCT) angiography technique. Methods: One eye from each subject was scanned with a 68 kHz Cirrus 5000 HD-OCT-based OMAG prototype system centered at the ONH (Carl Zeiss Meditec Inc, Dublin, CA, USA). Microvascular images were generated from the OMAG dataset by detecting the differences in OCT signal between consecutive B-scans. The pre-laminar layer (preLC) was isolated by a semi-automatic segmentation program. En face OMAG images for preLC were generated using signals with highest blood flow signal intensity. ONH perfusion was quantified as flux, vessel area density, and normalized flux within the ONH. Standard t-tests were performed to analyze the ONH perfusion differences between normal and glaucomatous eyes. Linear regression models were constructed to analyze the correlation between ONH perfusion and other clinical measurements. Results: Twenty normal and 21 glaucoma subjects were enrolled. Glaucomatous eyes had significantly lower ONH perfusion in preLC in all three perfusion metrics compared to normal eyes (P≤0.0003). Significant correlations between ONH perfusion and disease severity as well as structural changes were detected in glaucomatous eyes (P≤0.012). Conclusions: ONH perfusion detected by OMAG showed significant differences between glaucoma and normal controls and was significantly correlated with disease severity and structural defects in glaucomatous eyes. ONH perfusion measurement using OMAG may provide useful information for detection and monitoring of glaucoma.